Peningkatan keterampilan berbicara melalui media pembelajaran flash card mata pelajaran bahasa indonesia pada peserta didik kelas V sekolah dasar - Khoirani Lutfiana Putri; Siti Istiyati; Fadhil Purnama Adi (Universitas Sebelas Maret, 2020)
Abstract : This research was done to improve the speaking skills of fifth-grader state primary school Gumpang 3 of Sukoharjo in Academic Year 2017/2018 through the application of flash cards media.The research is an action classroom research by administering it in two cycles with 2 meetings per cycles. The stage of each cycle is planning, implementation . observation, and reflection. The subject in this research is fifth graders amount 34 students and their class teacher of State Primary School Gumpang 3 Sukoharjo. The technical of collecting data were used interview techniques, observation, documentation, and test. The data validation were used data source triangulation, data collection technique, and content validity. Technique for analyzing data were used the interactive model of analysis claimed by Miles and Huberman consisting of four phase, specifically: data collection, data reduction, data display, and conclusion of research.Based on the result of the research, reviewed on the minimal learning completeness criteria of 65 acumulation from 4 speaking aspect, in the pre-treatment the class average score was 43,75 with the classical learning completeness of 8,32%. Following the treatments at cycle I an increase has been made on the class average score became 67,1 with the classical learning completeness of 70,59%, then on the cycle II the class average score became 76,38 with the classical learning completeness of 85,29%. Thus can be drawn to the conclusion that the application of flash cards media could improve the speaking skill of the fifth-graders students of State Primary school Gumpang 3.Keywords: Flash Cards media, Speaking skill, Factual problem